Efficacy and safety of sorafenib versus apatinib in the treatment of intermediate and advanced hepatocellular carcinoma: a comparative retrospective study - Wang, Yizhuo (Onco Targets Ther, 2018)
OBJECTIVE: To compare the efficacy and safety profiles of sorafenib and apatinib in patients with intermediate- and advanced-stage hepatocellular carcinoma (HCC). METHODS: This was a single-center, retrospective study where we collected the clinical data of 72 patients, diagnosed with intermediate or advanced HCC from January 2014 to December 2016. Depending on the treatment received, 38 patients were categorized into group S (sorafenib group) and 34 into group A (apatinib group). The patients in group A received the initial recommended dose of 750 mg once daily (QD), which was reduced to 250 mg QD in the case of any class 3 or 4 adverse event (AE). Sorafenib was administered orally 400 mg twice daily (BID), and dose was modified to 400 mg or 200 mg QD in the case of grade 3 or 4 AEs. The median overall survival (OS), progression-free survival (PFS), and AEs reported in the two groups were analyzed and compared. RESULTS: Among the 38 patients treated with sorafenib, one patient had complete response (CR), 5 patients had partial response (PR), and 10 patients had stable disease (SD), and among the 34 patients treated with apatinib, 6 patients had PR and 7 patients had SD with no cases of CR. PFS in group S was significantly longer compared with that in group A (7.39 vs 4.79 months, respectively, P=0.031). Similar observations were made for median OS (10.4 months in group S vs 7.18 months in group A, P=0.011). However, there was no significant difference in the objective response rates (ORRs) among the study population (15.7 vs 17.6%, P=0.829). Common AEs in group S included hand and foot syndrome (HFS) and diarrhea, whereas common AEs in group A included hypertension, proteinuria, and increased transaminase. CONCLUSION: Our study showed promising clinical outcome with apatinib, but the sorafenib group exhibited better clinical efficacy with no significant difference in safety profile.